Representaciones de naturaleza de la ciencia en libros de texto de química: indagando por los tópicos epistemológicos de Representación y Lenguajes (2019)
We are sharing some ideas and theoretical supports that comes from a doctoral thesis, with the scientifi c community that is inquiring about the nature of the science fi eld (NOS). The goal of this work is to identify the epistemological time derives by NOS using two books, mainly in the representation and languages fi elds. Systematic networks were built in order to asses the textual statement derives from the books. no propositions related to Representation and Languages were found suggesting the absence or unclear thought about a NOS representation. These results have been already reported previously in other investigations. The highlight of this work is the proposal of the epistemology periodization, which is considered as a useful metascientifi c tool used for the characterization of NOS representation, with a better conceptual approach.